Advances in knowledge of inhibitor formation in severe haemophilia A. (17th February 2020) - Cormier, Matthew; Batty, Paul; Tarrant, Julie; Lillicrap, David
Summary: Anti‐drug antibody formation following factor VIII (FVIII) replacement therapy is the most important treatment‐related complication in patients with severe haemophilia A. A significant number of these antibodies show neutralising activity against FVIII and are referred to as FVIII inhibitors. Alloimmunity to FVIII, given the absence of endogenous circulating FVIII protein, may be predictable to some extent; however, only 30% of patients develop inhibitors. Genetic and environmental risk factors have been identified, contributing to the likelihood of inhibitor development. Multiple immunological theories have been proposed which in part explain the outcomes of many epidemiological studies. Significant differences exist among replacement therapies, including the source, FVIII sequence, glycosylation, formulation components, impurities and aggregation potential, which significantly complicate interpretation of the results from these studies. In this review, we present recent advances in the understanding of the cellular mechanisms of inhibitor formation and highlight some areas of uncertainty requiring further investigation.